"A Book Never Dies": The American Library Association and the Cultural Reconstruction of Czechoslovak and Polish Libraries, 1945–1948. (2nd January 2017) - Sroka, Marek
ABSTRACT: The American Library Association (ALA)'s role in the postwar cultural reconstruction of East Central European countries such as Czechoslovakia and Poland has not been widely studied. The paper contributes to a better understanding of American cultural influence in that part of Europe by examining the ALA's efforts of sharing the works of American culture and science with war-devastated libraries in the context of war losses suffered by Czechoslovak and Polish libraries and a rising tide of totalitarianism in Eastern Europe. Particular attention is given to individual requests for books and periodicals as they offer a firsthand account of the war devastation and an insight into various needs of Czechoslovak and Polish libraries in early postwar years.